PENGARUH PEMANFAATAN BIJI PEPAYA DAN MINYAK KELAPA TERHADAP PERUBAHAN WARNA RAMBUT BERUBAN - Budiman, Nanda Suci; Rostamailis, Rostamailis; Rahmiati, Rahmiati (Journal of Home Economics and Tourism, 2013)
This study aimed to analyze changes in the use of color gray hair with coconut oil and papaya seeds are assessed in terms of hair color. The study consisted of three different treatment control group, the experimental group the first and the second experimental group. The study was quasi-experimental study with the Nonequivalent Control Group Design and Engineering voluntary sampling was purposive sampling. Samples were five mothers who have never had hair coloring and have 25% gray hair. Data analysis is a variant analysis and Duncan test. The results showed that the change in hair color in the control group showed no change for the better in the indicator. In contrast, the experimental group the first and the second experimental group showed significant results in each indicator. As a result, the utilization of papaya seeds against gray hair color changes significantly with frequency eskperimen second best in the group that was mixed with coconut oil. Kata Kunci : biji pepaya, minyak kelapa, jenis penelitian, kelompok penelitian.